A STRATEGY TO STRENGTHENING THE HUMAN RESOURCE CAPABILITIES AS A VALUABLE POTENCY TOWARD CREATIVE INDUSTRY DEVELOPMENT IN SOUTH TANGERANG - Putri, Caecaria Dwi; Hidayat, Nila K. (Emerging Markets : Business and Management Studies Journal, 2013)
Human resource capability is esseltial to develop the creative industry in South Tangerang since if the human capability is lacking, it will affect the output of organization and also the other capability will be at risk. The first purpose of this research is to analyze whether there is a strong influence between human resource capabilities to the development of creative industry. The second purpose is to identify the most significance capability toward creative industry development. The third is what strategy should be implemented to develop HR Resources to Creative Industry. Descriptive research is used as a type of study which followed by qualitative and quantitative method. Furthermore, the data is analyzed though the Structural Equation Modeling analysis (SEM). The findings of this research shows that human resource capability has a strong influence to the development of creative industry in South Tangerang with the highest contribution is from skill and the strategy generated is more focused on strengthening skill as the most potential capability of people. Based on the findings, recommendation generated is government and creative industry business owner should pay more attention to the people capability and create a specific strategy and vision to srengthening the people capability.